KEPATUHAN REMAJA SMA NEGERI DI KOTA DENPASAR TERHADAP KESELAMATAN BERKENDARA (SAFETY RIDING) SEPEDA MOTOR - Sinuraya, Egiya Goldarosa; Wirawan, I Made Ady; Duana, I Made Kerta (ARCHIVE OF COMMUNITY HEALTH; Vol 5 No 1 (2018): Juni (2018)DO - 10.24843/ACH.2018.v05.i01.p07, 2020)
ABSTRACT Traffic accidents are a global problem and the case increase significantly every day, so we need to know the compliance of riders, especially riders about safety riding related to safety riding knowledge. The World Health Organization states that traffic accidents are the main cause of adolescent mortality in the world at the age range of 15-29 years. This study aims to determine the description of adolescent compliance with safety riding compliance in state high schools in Denpasar. This research is a quantitative descriptive study with cross-sectional design. The research sample consisted of 350 respondents using a multistage random sampling technique. Data collection was carried out by means of interviews using questionnaires and documentation studies and then the data obtained was processed using STATA software. The results showed the level of adolescent knowledge of safety riding compliance included in the high category, as many as 170 respondents (69.96%) and the attitudes of respondents towards safety riding compliance had a positive attitude of 157 respondents (70.40%). Compliance about safety riding is included in the category of compliance, as many as 241 respondents (68.86%). Based on the results of statistical tests found that there is a significant relationship between sex with safety riding compliance (p = 0.03). Female respondents, namely 147 respondents (73.50%) were more obedient to safety riding than male respondents. School and the authorities must doing socialization and education about the importance of safety riding. In addition, adolescents need to increase knowledge about safety riding and foster safety riding behavior through fostering traffic discipline and finding information about safety riding in the mass media and the internet. Keywords: Knowledge Level, Safety Riding, Compliance, Teenagers